Running a ring of spies spycraft and black operations in the real world of espionage - Mack, Jefferson (Paladin Press, 1996)
Running a ring of spies is no mission impossible with this tell-all primer. Find out the secrets of the world's best spies and peep into the real world of a Bangkok madam-turned-secret agent, Aldrich Ames, U.S. Embassy guards, Kim Philby and garden-variety corporate spies. Find out how to get the goods on the bad guys.